PELAKSANAAN PEMANCANGAN FONDASI TIANG PANCANG METODE JACK-IN PILE PADA PERKUATAN FONDASI KONSTRUKSI SARANG LABA â LABA (KSLL) BANGUNAN BNI 46 WILAYAH 05 SEMARANG - , INTAN CESARIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The type of soil with all the technical soil characteristic is an important factor that must be considered in foundation design to prevent failure on building construction. Settlement is one of failure building construction that often occur, due to consolidation. Upper structure failures occurred in Building Bank Negara Indonesia (BNI) 46 Regional Office â05 Semarang. Based on the results of soil tests estimated that the soil is experiencing consolidation symptoms. Results of research and evaluation as a result of a decrease in BNI 46 building Regional Semarang â05 showed the need for improvement and re-design is to strengthen the foundation structure made of pile concrete with dimensions 25 x 25 cm at a depth of 30 m, so after the foundation KSLL added to dolcent / timber and foundation KSLL increasingly solid and increase strength and more compact. Technological developments in the world of construction is in line to the development of a tools that was created to assist and facilitate the construction activity. Project environmental factors surrounding buildings and locations in the room, minipile reinforcement concrete pile foundation will be done by the method of jack-in pile. Jack in pile is a pile foundation system whose implementation erection pressed enter into the soil using a hydraulic jack that loaded by Counterweight or reaction system so as not to cause vibration and noise. The tools used in the Jack â in Pile method is Hydraulic Static Piling Driver (HSPD) capacity of 60 tons and 90 tons. The applications of strengthed minipile foundation in BNI 46 building Region â05 Semarang with Jack â in Pile method are preparatory work and determination of the point to be put up, the reaction system or counterweight installation, piling minipile pressed the manner specified pressure while governed the verticality, splicing minipile the way welded, and finishing piling. The advantages of the method of Jack-in Pile is free vibration , free air pollution, and free noise, free contamination work sites, known carrying capacity pile, can work on the job site is limited. While the weakness of the method of Jack-in Pile is space for tools and loading capacity is limited by space, long duration because it requires splicing minipile, and the cost is more expensive.